SOCIAL COGNITIVE INDICATORS ON MENTAL HEALTH OF EMPLOYED YOUNG ADULTS IN MALAYSIAN BANKING SECTOR - Nurfarah Diyana Binti Khairul Azman; Dr Rachel Samuel; Dr Idris Osman (International Journal of Accounting, Finance and Business, 2021)
Mental health refers to our cognitive, behavioral, and emotional well being which is all about how we think, feel, and behave. The strength of a person’s mental health has a direct link to the capability of a person to perform a variety of everyday tasks and activities. This includes the capability of a person to learn, feel and communicate a wide array of emotions as well as the capability in establishing and sustaining good relationships with others in day-today- dealings. Global economy and deregulated markets have led to changes in the way financial services are performed, and this is particularly true of the organization and execution of work in this sector. These changes have caused mental health issues in many young, employed people. This paper uses indicators based on the Social Cognitive Theory (SCT) to identify factors associated with mental health of young people. Cognitive, behaviour and the environment are the primary components of SCT. Various elements define each of these components. Elements in the cognitive component are knowledge, expectations and attitudes. Meanwhile behaviour elements are skills, practices and self efficacy. Lastly environment elements are social aspects, social support and physical factors. Given the emphasis on the individual and the environment, SCT has been widely used in health promotion. SCT considers the unique way in which people acquire and retain behaviour, while also considering the social environment in which the behaviour is carried out by individuals.